Consumer Protection in the Retail and Financial Services Sectors against the Practice of Exoneration Clauses - Anna Maria Tri Anggraini; Megawati Simanjuntak; Arief Safari; Rizal E. Halim; Slamet Riyadi (Journal of Consumer Sciences, 2022)
The rapid development of the business world has resulted in several changes to business actors in carrying out their business activities. This encourages the emergence of standard agreements as practicality in conducting transactions. This study aims to analyze consumer protection law and apply the principles of freedom of contract in standard agreements in online and retail financial services businesses—the descriptive qualitative method with data collection techniques using in-depth interviews and documentation studies. Informants were selected by purposive sampling. The results show that standard clauses have been regulated in Article 18 of the Consumer Protection Law. However, in practice, clauses are still found that violate and transfer responsibility to the detriment of consumers. Furthermore, regarding consumer dispute resolution, there is an overlap issue between the Financial Services Authority (OJK) and the Consumer Dispute Resolution Agency (BPSK). Therefore, if viewed from the principle of freedom of contract, the standard agreement cannot fulfill the principle of freedom of contract, and consumer protection, so especially in the financial services sector and retail, needs to increase preventive and repressive supervision by providing several alternatives dispute resolutions for disadvantaged consumers.